Role of Pastoral Care on Church Growth: A Case Study of Muko Parish Rubanda District. - Ampumuza, Flavia (Kabale University, 2025)
The study assessed the contributions of pastoral care on church growth. A case study of Muko parish Rubanda district following the objectives of the study which were to find out the services offered by pastoral care to the church growth of Muko district, to explore the challenges faced by pastoral care in the transformation of the Christian community in Muko parish Rubanda district and to find out possible strategies that promote pastoral care in the transformation of the Christian community of Muko parish Rubanda district. A descriptive research design was used and data collection tools were both interviews and questionnaires. A sample of 80 respondents was used for the study. Results of the study revealed that Spiritual Counselling and Community outreach are needed as well. The study concluded that leadership development emerged as the most critical service, reflecting its pivotal role in enhancing church effectiveness and growth. The emphasis on training and mentoring aligns with literature that underscores the importance of strong leadership in driving church success. Marriage and Family Support and Home Visitation were also highly valued, highlighting the need for personal and relational support in fostering a cohesive and engaged congregation. These services are well-supported by literature, which emphasizes their role in member satisfaction and retention. Prayer and Healing Services, Community Outreach, and Youth and Children's Ministry were important but less emphasized. These services contribute to church vitality and align with best practices for engaging different segments of the community. The study recommended that the church leaders from the church council in Muko Parish like other leaders in development, and community leaders in Uganda should collaborate with political leaders to have a keen direction of rural development by facilitating rural communities with education services in the form of building schools and paying school fees for students at different levels within Muko Parish.